2010
DOI: 10.1111/j.2040-1124.2010.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Acarbose treatments improve arterial stiffness in patients with type 2 diabetes mellitus

Abstract: Aims/Introduction:  Although the improvement of postprandial hyperglycemia by an alpha‐glucosidase inhibitor (α‐GI) has been associated with a risk reduction of cardiovascular events, the relationship between postprandial hyperglycemia and arterial stiffness has not been well understood. We therefore examined whether ameliorating the postprandial state by α‐GI leads to an improvement in arterial stiffness.Materials and Methods:  A total of 22 patients with type 2 diabetes mellitus were treated with acarbose. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
0
17
2
3
Order By: Relevance
“…Acarbose treatment reduces the risk of cardiovascular disease by altering the arterial stiffness in the postprandial hyperglycaemic status in patients with type 2 diabetes. In this study a significant reduction in cardio-ankle vascular index (a parameter of arterial stiffness) was shown, although the changes in blood pressure and heart rate were not significant 84 . 86 .…”
Section: Peroral Antidiabetic Drugscontrasting
confidence: 58%
“…Acarbose treatment reduces the risk of cardiovascular disease by altering the arterial stiffness in the postprandial hyperglycaemic status in patients with type 2 diabetes. In this study a significant reduction in cardio-ankle vascular index (a parameter of arterial stiffness) was shown, although the changes in blood pressure and heart rate were not significant 84 . 86 .…”
Section: Peroral Antidiabetic Drugscontrasting
confidence: 58%
“…The values of CAVI are sometimes influenced by the glucose-lowering treatment; there are some glucoselowering treatments that lower CAVI and others that do not 65) . Alpha-glucosidase inhibitor, acarbose, reduces CAVI mediated by an improvement of postprandial hyperglycemia 66) . Ohira et al 67) reported that switching biphasic insulin from human insulin 30/70 to insulin aspart 30/70 improved CAVI together with the marker of postprandial hyperglycemia.…”
Section: Treatment Of Diabetes Mellitusmentioning
confidence: 99%
“…Так, отмечается независимая ассоциация CAVI с постпрандиальной гликемией [23,24], с уровнем гликированного гемоглобина (HbA 1c ) [9,19]. Кроме того, снижение HbA 1c на фоне компенсации СД существенно коррелировало с улучшением значений CAVI [9].…”
Section: осложненияunclassified
“…Кроме того, снижение HbA 1c на фоне компенсации СД существенно коррелировало с улучшением значений CAVI [9]. В лите-ратуре отмечено влияние длительного приема различных препаратов на снижение CAVI [23,24,25].…”
Section: осложненияunclassified
See 1 more Smart Citation